2021
DOI: 10.1089/heq.2020.0097
|View full text |Cite
|
Sign up to set email alerts
|

Gender Equity and Vertically Transmitted Infections: A Country-Level Analysis Across 153 Countries

Abstract: Purpose: Gender inequality is a barrier to education toward women and accessibility to health facilities, which are important for preventing vertical transmission. This study was conducted to analyze the impact of gender equity on vertically transmitted infections (hepatitis viruses, human immunodeficiency virus [HIV], and syphilis) using country-level indicators. Methods: The relationship between the Global Gender Gap Index (GGGI), which is indicator of gender equity, and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…This is because if women cannot avail the facilities of these programs, these efforts are futile. Other researches have also shown that reducing gender gaps decreases the vertical transmission of HIV (Lee et al, 2021). Women empowerment is a crucial aspect in reversing the HIV epidemic (Carr, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This is because if women cannot avail the facilities of these programs, these efforts are futile. Other researches have also shown that reducing gender gaps decreases the vertical transmission of HIV (Lee et al, 2021). Women empowerment is a crucial aspect in reversing the HIV epidemic (Carr, 2008).…”
Section: Discussionmentioning
confidence: 99%